Heparin induces harmless fibril formation in amyloidogenic W7FW14F apomyoglobin and amyloid aggregation in wild-type protein in vitro. - Silvia Vilasi; Rosalba Sarcina; Rosa Maritato; Antonella De Simone; Gaetano Irace; Ivana Sirangelo (PLoS ONE, 2011)
Glycosaminoglycans (GAGs) are frequently associated with amyloid deposits in most amyloid diseases, and there is evidence to support their active role in amyloid fibril formation. The purpose of this study was to obtain structural insight into GAG-protein interactions and to better elucidate the molecular mechanism underlying the effect of GAGs on the amyloid aggregation process and on the related cytotoxicity. To this aim, using Fourier transform infrared and circular diochroism spectroscopy, electron microscopy and thioflavin fluorescence dye we examined the effect of heparin and other GAGs on the fibrillogenesis and cytotoxicity of aggregates formed by the amyloidogenic W7FW14 apomyoglobin mutant. Although this protein is unrelated to human disease, it is a suitable model for in vitro studies because it forms amyloid-like fibrils under physiological conditions of pH and temperature. Heparin strongly stimulated aggregation into amyloid fibrils, thereby abolishing the lag-phase normally detected following the kinetics of the process, and increasing the yield of fibrils. Moreover, the protein aggregates were harmless when assayed for cytotoxicity in vitro. Neutral or positive compounds did not affect the aggregation rate, and the early aggregates were highly cytotoxic. The surprising result that heparin induced amyloid fibril formation in wild-type apomyoglobin and in the partially folded intermediate state of the mutant, i.e., proteins that normally do not show any tendency to aggregate, suggested that the interaction of heparin with apomyoglobin is highly specific because of the presence, in protein turn regions, of consensus sequences consisting of alternating basic and non-basic residues that are capable of binding heparin molecules. Our data suggest that GAGs play a dual role in amyloidosis, namely, they promote beneficial fibril formation, but they also function as pathological chaperones by inducing amyloid aggregation.